Self-reported overeating and attributions for food intake. Issue 4 (3rd April 2017) - Vartanian, Lenny R.; Reily, Natalie M.; Spanos, Samantha; Herman, C. Peter; Polivy, Janet
Abstract : Objective: We examined whether people's attributions for their eating behaviour differ according to whether they believe they have eaten more, less or about the same as they normally would. Design: Participants were served a small or large portion of pasta for lunch. Afterwards, they were asked to compare how much they ate in the study to how much they normally eat for lunch, resulting in three intake-evaluation categories: 'ate less', 'ate about the same' or 'ate more'. Main outcome measures: How much participants ate; the extent to which they attributed their food intake to an internal cue (i.e. hunger) and an external cue (i.e. the amount of food served). Results: Participants served a large portion ate more than those served a small portion, but the magnitude of the portion-size effect did not vary across intake-evaluation categories. Furthermore, although participants in all groups indicated that their hunger influenced how much they ate, only those in the 'ate more' group indicated that the amount of food available influenced how much they ate. Conclusion: People appear to be willing to explain their food intake in terms of an external cue only when they believe that they have eaten more than they normally would.